(untitled) (Indian Journal of Nematology, 2024)
Rice root-knot nematode Meloidogyne graminicola is a destructive plant parasitic nematode that significantly affects rice production worldwide. Endophytic bacteria confer resistance against nematodes through the production of various bioactive molecules. In the present study, the bioactive molecules produced by Bacillus cereus were evaluated against the potential protein targets of M.graminicola, such as Metalloendopeptidase, MgGPP, MgM0237, MgPDI1, MgPDI2, MgPEL1 and Mg-vap1 (venom allergenlike protein) by employing molecular docking techniques. The study revealed that all the bioactive molecules had a significant impact on the protein targets of M. graminicola. Among the 12 biomolecules, Picoxystrobin and 3-Deoxy-d-mannonic acid had a dominant effect on various protein targets through molecular docking approaches, and these biomolecules from B. cereus can be explored as the novel nematostatic molecules against M. graminicola.